Infecciones por Staphylococcus aureus resistente a la meticilina adquirido en la comunidad en pacientes de Villavicencio, Colombia (2016)
Introduction: Staphylococcus aureus is a very versatile pathogen, with a capacity to cause a great range of conditions in humans. However, the role played by its virulence factors in the development of infection is not thoroughly understood. Some clonal types are very well equipped to cause disease in all persons, whereas others only affect some members of a community. Objective: Determine the prevalence of community-acquired methicillin resistant Staphylococcus aureus infections in patients from the city of Villavicencio in Colombia. Methods: A descriptive cross-sectional prospective study was conducted of 46 samples obtained from abscesses, secretions, blood, urine, pericardial fluid, pleural fluid, tracheal aspirates and boils. Participants had not been hospitalized in recent months nor had they received any antimicrobial treatment, and they did not present any clinical signs and/or symptoms. The isolates were identified by means of conventional microbiological tests. Antimicrobial susceptibility to the various antibiotics was determined using MicroScan™ Pos Combo Panel Type pc 24 (Dade Behring, USA). The genes nuc, mecA and LukS-PV were detected. These are related to the identification and virulence of the study species. Results: Of the 46 samples analyzed, 46 (100%) were positive for S. aureus, 46 (100 %) were resistant to methicillin and 44 (95.6%) contained the LPV gene. Conclusions: In Colombia and specifically in Villavicencio, little is known about the epidemiology of CA-MRSA. Epidemiological screening and molecular typing studies should be conducted to gain insight into the epidemiology of CA-MRSA and design better prevention and control strategies. © 2016, Editorial Ciencias Medicas. All rights reserved.